Internalized Homonegativity and Psychological Distress in Lesbian, Gay, and Bisexual Individuals : Self-compassion as Mediator - Dicky Sugianto; D.P. Budi Susetyo; George Hardjanta (PSIKODIMENSIA, 2019)
Internalized homonegativity has been well documented to associate with psychological distress. Previous studies have found various factors which mediated the relationship between the two variables. The current study aimed to explore other factor which mediates the two variables, namely self-compassion. Participants were lesbian, gay, and bisexual individuals who recruited via online survey (N = 55). Data was analyzed using few steps of regression analysis. The results show that internalized homonegativity is not related to psychological distres and self-compassion in current sample. Self-compassion is found to be significantly predict psychological distress (F(1,53) = 25,140, p < 0,01; R2 = 0,322), which affirms previous findings. Results imply that lesbian, gay, and bisexual individuals can exercise self-compassion to cope with psychological distress arising from their minority status.